Health Risks of Climate Change and Variability to Maternal Health - Mashara, Janet Naisoi; Thuranira, Mercy; Kathambi, Fridah (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Climate change has emerged as a significant global challenge with far-reaching implications for human health. Through a comprehensive review of scholarly articles, the study examines the complex interplay between climate change and maternal health and highlights the role of religion in climate change mitigation. Mothers play an integral role in creating and sustaining healthy households. Furthermore, improving maternal health is essential to achieving global sustainable development goals, particularly goal 3 (Good Health and Well-being). The paper sought to examine the physical and psychosocial effects of climate change on expectant mothers. The study explored the following objectives: the direct impacts of climate change on maternal health; Indirect impacts of climate change on maternal; and mitigation strategies. The study revealed that, rising temperatures and heatwaves increase maternal heat-related illnesses, potentially affecting birth outcomes. Vector-borne diseases, influenced by climate shifts, pose additional threats to maternal well-being. Environmental stressors, including natural disasters and climate-related migration, contribute to maternal stress, anxiety and depression affecting maternal care. Christian teachings acknowledge human life as precious and sacred. It should be protected and valued from conception until death. Religious beliefs and values lay emphasis on stewardship of the environment, social justice, compassion, and community support. Religious institutions and leaders can play pivotal roles in advocating for climate action, promoting sustainable practices, and providing psychosocial support to individuals and families affected by climate-related health issues. To effectively combat climate change effects, the study recommends that it is imperative to embrace integrated approaches that prioritize healthcare access, environmental resilience, mental health support, and community-based initiatives that integrate religious perspectives with scientific knowledge and best practices.